Estimation of Oxidative Stress Markers and Immune Response in Patients with Salmonella Typhi Infection: Penilaian Marker Stres Oksidatif dan Respons Imun pada Pasien dengan Infeksi Salmonella Typhi - Al-Zubaidy, Zainab H. (Indonesian Journal on Health Science and Medicine, 2025)
Background: Oxidative stress has an important role in the pathogenesis of Salmonella Typhi infection, disrupting host defense and contributing to tissue damage. Specific Background: Assessing oxidative stress markers together with immune response indicators may provide a clearer understanding of disease severity and host–pathogen interactions. Knowledge Gap: However, limited evidence exists on how these markers correlate and contribute to the progression and severity of typhoid fever. Aims: This study aimed to evaluate oxidative stress markers (MDA, TAC, SOD, GSH) and immune response parameters (IL-6, TNF-α, CRP, WBC) in patients with confirmed S. Typhi infection compared with healthy controls. Results: Patients showed significantly higher MDA, IL-6, TNF-α, CRP, and WBC levels, with reduced antioxidant indices, and strong correlations between oxidative stress and inflammatory mediators. Severe cases exhibited the highest oxidative and inflammatory imbalance. Novelty: This study demonstrates a direct relationship between oxidative damage and immune activation in typhoid fever. Implications: These biomarkers could serve as diagnostic and prognostic indicators, supporting the development of adjunctive therapies that restore oxidative–immune balance.Highlight : Infection increases oxidative stress and reduces antioxidant capacity. Elevated IL-6, TNF-α, and CRP indicate a strong inflammatory response. The relationship of biomarkers with severity is useful for prognosis. Keywords : Salmonella Typhi, Oxidative Stress, Antioxidants, Immune Response, C-Reactive Protein